Resource efficiency technology of purification of industrial wastewater from nickel - Zoria О.; Ternovtsev, O.; Zoria, D. (Ways to Improve Construction Efficiency, 2019)
The technology of treatment of wastewaters containing nickel with the use of worked out industrial solutions - iron-containing solutions, from which ferromagnetic reagents have been obtained, is offered. Different formulations of reagents have been investigated and the most optimal reagent, which includes magnetite and sodium silicate, is selected.